(untitled) (ACME, 2020)
Francesco’s views on time remains original : his Compilatio as the second book of Sentences seem to be influenced by the commentators of the XIIIth century but by his contemporaries of XIVth century too. The aporetic nature of successive quantitative beings, the unity of time, his mathematical ontology, like his relative being to the first celestial motion are enough of essential elements and subject matter discussed by the Doctor Succinctus. From this subtle alliance of these different traditions of using geometry, stressing the increasing importance of the category of quantity, or the ontological reduction of time and motion appears a singular conception of an actual infinite, which is composed by entities in act and represents eternity and divine creation.